Rob Delaney : mother, wife, sister, human, warrior, falcon, yardstick, turban, cabbage - Delaney, Rob, 1977- (Spiegel & Grau, 2013)
"Rob Delaney is the raunchiest feminist you'll ever meet. But if you're one of the 788,000 people who follow him on Twitter, you already know that. Delaney has made the 140 character tweet into a comic art form and that talent--along with the hilarious and painful sharing he does in his stand-up--has made him a white-hot comedy superstar. Tackling subjects from his youthful obssession (and pen pal relationship) with heavy metal band Danzig to drunken bungee jumping off the Brooklyn Bridge, from his court-ordered stint in rehab to witnessing the miracle of his son's birth, these essays meanderingly trace Rob's journey from middle class theater geek, to public menace, to devoted family man and passionately engaged model citizen. All together, these essays (interspersed with some of his "Greatest Tweets") make clear why it is he is so darn lovable and so f♯!%ing funny"--